Magnetization dynamics of domain wall based devices for logic and memory applications - Sethi, Pankaj (2017)
The ever increasing digital data require memory and logic devices that have high speed, need low power, offer low cost and are reliable. Domain wall (DW) based memory and logic devices potentially offers all the above advantages along with being non-volatile. In this thesis, the dynamics of DWs have been investigated in ferromagnetic nanostructures for realizing efficient logic and memory based applications. The study has been divided into two parts. In part one, the DW dynamics in ferromagnetic network structures with in-plane magnetic anisotropy (IMA) is studied. The magnetic material chosen is NiFe due to its large magnetic permeability and near zero crystalline anisotropy. In part two of the study, materials with perpendicular magnetic anisotropy (PMA) are considered. Here, Co/Ni and Co/Pt multilayers are chosen as the system for study. Field induced domain wall driving in IMA network structures revealed the DW trajectory to be chirality dependent. Deterministic trajectory of DW in the network structure is demonstrated for path lengths less than the fidelity length and for fields less than Walker breakdown field. For distances in excess of fidelity length, Walker breakdown is observed where DW chirality is found to oscillate and the trajectory becomes stochastic. To overcome this issue, the network structures are re-designed to include geometrical asymmetry. This constrains DW to propagate in a definite and fixed branch, by raising the potential barrier in the other branch, irrespective of its chirality. This branch engineering is applied to propose and demonstrate a programmable logic device. The control of the trajectory is provided by fabricating a metallic gate on top of the network structure. The current in the gate applies an Oersted field which influences the trajectory of DW by interacting with the transverse charge distribution in the DW. A transverse nanowire in the structure serves a dual purpose of acting as an input logic and also transforming the vortex DW to a transverse chirality. Two universal logic gate functionalities NAND and NOR are demonstrated along with the complimentary logic operations in the same structure using magnetic force microscopy imaging and anisotropic magneto-resistance. The PMA system is investigated using the phenomena of anomalous Hall effect. Our investigations reveal multiple DW nucleations in low anisotropy Co/Ni Hall cross junctions under the application of in-plane current without the need of conventionally used local Oersted field. The stochasticity in the nucleation process due to high demagnetization energy at the Hall cross coupled with joule heating is utilized to demonstrate a DW based random number generator device. The analog signal from the device is fed to an integrated circuit to amplify and digitize the output. Recent developments have shown combination of interfacial phenomenon such as spin-orbit torque (SOT) and Dzyloshinskii-Morya interaction leading to high speed DW dynamics. Pt/Co/Ta stacks have enhanced SOT strength due to opposite signs of spin Hall angle of Ta and Pt. However, it is observed that stack possesses low thermal stability due to reported intermixing of Ta and Co. A solution to this issue is provided by adding additional Co/Pt interface which enhances the thermal stability and PMA strength. The distribution in velocity with the applied current density and spin Hall angle is estimated by changing the Ta capping thickness and Pt spacer thickness. SOT driven DW speed of about 530 m/s at a current density of 1×1012 A/m2 is demonstrated. This high speed is attributed to low anisotropy of our device coupled with in-plane field applied to prevent Walker breakdown. DW velocity was higher and along the current flow direction when the in-plane field assisted the inherent DMI field, while it was lower and along the electron flow direction when the field opposed the DMI field.